Correlates of time to microvascular complications among diabetes mellitus patients using parametric and non-parametric approaches: a case study of Ayder referral hospital, Ethiopia - Berihun, Lewtnesh; Kebede, Essey (Ethiopian Journal of Science and Technology, 2025)
Socio-demographic and clinical factors have been known to affect the time to microvascular complications and survival probabilities of diabetes mellitus patients. The objective of this study was to identify risk factors and estimate average survival times for the time to the development of microvascular complications of diabetic patients under follow up at Ayder referral hospital from February 2011 to January 2014. A retrospective follow up study was conducted on diabetic patients during this treatment period of 3 years. Using simple random sampling a total of 277 patients were included in the study. Cox and Weibull proportional hazards models were used to identify risk factors for the time to microvascular complications. Results showed that the prevalence of microvascular complication during the follow up period in the studied population was 42.6% and was more prevalent in women. The estimated overall median survival time was 425 days. Factors associated with increased risk of microvascular complications among the sampled diabetes mellitus patients as identified by the Weibull model were older age (HR=1.025, 95% CI: 1.008-1.043, p=0.003), female sex (HR=1.531, 95% CI: 1.063-2.206, p=0.002), Type 2 diabetes (HR=2.320, 95% CI: 1.121-4.799, p=0.023) and fasting blood sugar (FBS) (HR=1.006, 95% CI: 1.003-1.008, p=0.0000). The results suggest strongly that to minimize the risk of diabetic complications it is necessary to treat blood glucose aggressively.